Language Variation in Arabic among University Students: Sociolinguistic Challenges and Pedagogical Opportunities in a Multicultural Classroom - Harahap, Desi Hariyanti; Jumahir, Al Magfira; Budianto, Langgeng (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to describe the linguistic variations in Arabic usage among students of the Arabic Language Education Program, Class E, 2024 cohort, consisting of 15 students, and to identify the contributing factors and challenges in Arabic language learning. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and document analysis. The findings reveal that students' use of Arabic is highly diverse, encompassing variations in dialect, function, formality, and communication medium. These variations are influenced by students’ educational backgrounds (e.g., salafi and modern Islamic boarding schools, state Islamic high schools), regional origins, as well as technological and cultural developments. In practice, students frequently combine fusha, 'amiyah, and elements of Indonesian or regional languages in daily interactions. The study also highlights the challenges of curriculum harmonization, the shortage of qualified Arabic teachers, and the necessity for inclusive and intercultural teaching approaches. These findings underscore the sociolinguistic reality that language variation reflects students' social identities and interactional dynamics. Therefore, adaptive and context-sensitive strategies are required to develop Arabic language instruction that is both linguistically effective and culturally relevant in a multicultural academic environment.